Critical Thinking Ability in Translation 5 Course Online Tutorials - Nur Hasanah (Green Publisher Indonesia, 2022)
This study aims to determine students' critical thinking skills in online tutorials for translation 5 courses. The research method used is a qualitative descriptive method using an assessment rubric proposed by Finken and Ennis (1993). The results showed that there were still at least 2 students who were able to demonstrate critical thinking skills in discussions 1,3, and 4 in the online tutorial for the Translation course 5. In discussion 1 only 2 students out of a total of 31 students showed good development in critical thinking skills and in discussion 3 , only 1 out of 26 students have the same development of critical thinking skills. The same thing is also seen in discussion 4, only 2 students out of a total of 27 students have good development. Therefore, critical thinking skills in online tutorials for translation 5 courses still need to be improved.